Os intelectuais da libertação e o intercâmbio educativo: uma leitura gramsciana da Revista Eclesiástica Brasileira (1972 - 1986) - Reis, Egberto Pereira dos (2014)
This thesis has, as research objective, the Eclesiastic Brazilian REB Magazine,during the period 1972-1986, and how a group of intellectuals interacts in a specific ideology, establishing an educational proposal together with the Basic Ecclesial Communities (BECs). It was raised the hypothesis that the magazine can be a source of understanding and a diffusing way of the intellectual and moral reform and, also, an instrument in search of hegemony. Therefor, as a theoretical reference, it was used Antonio Gramsci s way of thinking, who, in his work Caderno do Cárcere developed a valuable study of magazines. For Gramsci, the importance of the magazines exceeds the purely academic question constituted of the dialectical relationship between intellectuals and working class. It was used, mainly, the concept of war for position to understand the quest for hegemony within the church and state. Thus, this thesis aims to explain how the ideology of libertation of theology was elaborated, explaining its main sources and currents of thoughts, that offer theoretical soundness to this theology. To understand the educational principle, it was analyzed, starting from the concept of positional war, how are waged the hegemony disputes regarding the intellectuals from REB, in a confrontation with the civil society and with the church structure itself. Thus, the concept of organic intellectual was the foundation to identify the intellectuals who published in the magazines and acted in the civil society. The identification of these actors contributed to analyze which disputes were conducted and if in fact, happened the exchange of knowledge, producing, this way, the educational principle. The methodology used was the bibliographic literature having as main source the magazine itself with its editorials and articles. The bibliometric analysis was also used as a way to measure the magazine gathering important informations to understand the type of intellectual his titration on the issues addressed forming a group with the same liberating bias. The thesis seeks to demonstrate, through REB, the existence of a group,that forms a relatively cohesive movement in the search for political, economic and social liberation. In order to do so, it was set up an educational relationship between the people of CEB and the intellectuals, this is the educational principle elaborated by Antonio Gramsci. As a result the education/educator experience was required for the exchange of knowledge between the intellectual and regular people establishing this way, the educational reciprocity. The consequences of these disputes were the presence of a theology that became a reference for intellectual production and especially it identifies itself with the people of BEC in a dialectical party movement according to the Gramsci s notion.The intellectuals of REB, together with people of the grassroots communities formed a Party committed to the social issues in an attempt to change the superstructure.